Implementasi Pendidikan Sekolah Dasar Islam Terpadu (SDIT) Adzkia 4 Palabuhanratu - Cacang Cacang; Siti Qomariah; Ridwan Hermawan; Hasbullah Karim Alfauzi (Lembag, 2025)
This study examines the implementation of the integrated Islamic education concept at SDIT Adzkia 4 Palabuhanratu. Integrated Islamic education combines religious and general knowledge using a holistic approach to develop students with noble character, broad insight, and readiness to face global challenges. Employing a qualitative method with a descriptive approach, the study gathers data through interviews, observations, and document analysis. The findings reveal that SDIT Adzkia 4 effectively integrates Islamic values with general subjects, fostering students' spiritual and intellectual growth. Teachers play a pivotal role in balancing these aspects, while parental involvement through intensive communication with the school significantly supports educational success. Challenges identified include limited resources, teacher readiness gaps, and difficulties in maintaining consistent integration of Islamic values across learning processes.The study underscores the need for improved teacher training to enhance their competence in delivering materials holistically and innovatively. Despite challenges, SDIT Adzkia 4 has succeeded in shaping a generation that excels intellectually while upholding strong religious values. Strengthening collaboration between the school and parents is crucial to optimizing the implementation of integrated Islamic education, ensuring that students are well-prepared for global challenges while rooted in their Islamic identity.